A multiscale study of fungal endophyte communities of the foliar endosphere of native rubber trees in Eastern Amazon. Issue 1 (December 2018) - Vaz, Aline; Fonseca, Paula; Badotti, Fernanda; Skaltsas, Demetra; Tomé, Luiz; Silva, Allefi; Cunha, Mayara; Soares, Marco; Santos, Vera; Oliveira, Guilherme; Chaverri, Priscilla; Góes-Neto, Aristóteles
Abstract Hevea brasiliensis is a native hyperdiverse tree species in the Amazon basin with great economic importance since it produces the highest quality natural rubber.H .brasiliensis, in its natural habitat, may harbor fungal endophytes that help defend against phytopathogenic fungi. In this work, we investigated the fungal endophytic communities in two pristine areas in Eastern Amazon (Anavilhanas National Park – ANP and Caxiuanã National Forest – CNF) at different spatial scales: regional, local, individual (tree), and intra-individual (leaflet). Using a culture-based approach, 210 fungal endophytes were isolated from 240 sampling units and assigned to 46 distinct MOTUs based on sequencing of the nrITS DNA. The community compositions of the endophytomes are different at both regional and local scales, dominated by very few taxa and highly skewed toward rare taxa, with many endophytes infrequently isolated across hosts in sampled space.Colletotrichum sp. 1, a probably latent pathogen, was the most abundant endophytic putative species and was obtained from all individual host trees in both study areas. Although the second most abundant putative species differed between the two collection sites, Clonostachys sp. 1 andTrichoderma sp. 1, they are phylogenetically related (Hypocreales) mycoparasites. Thus, they probably exhibit the same ecological function in the foliar endosphere of rubber tree as antagonists of its fungal pathogens.